Estructuración y elaboración del manual de los procesos y procedimientos en la empresa "DIFIORI S.A." - Barrero Albuja, Blanca Karina (2011)
The formalization and documentation of processes and procedures makes an organization more efficient considering it as an interrelated system, where any modification of its parts affects the entire company and that the processes are dynamic and complex. On the other hand can generate a standardized to learn how to collect and classify information processes avoiding the presence of conflicts that prevent bringing the product to the customer in the conditions it requires medium.